A Post-Mortem Empirical Investigation of the Popularity and Distribution of Malware Files in the Contemporary Web-Facing Internet - Jukka Ruohonen; Sanja; Scepanovic; Sami Hyrynsalmi; Igor Mishkovski; Tuomas Aura; Ville Leppänen (My University, 2022)
This short empirical paper investigates a snapshot
of about two million files from a continuously updated big
data collection maintained by F-Secure for security intelligence
purposes. By further augmenting the snapshot with open data
covering about a half of a million files, the paper examines two
questions: (a) what is the shape of a probability distribution
characterizing the relative share of malware files to all files
distributed from web-facing Internet domains; and (b) what is the
distribution shaping the popularity of malware files? A bimodal
distribution is proposed as an answer to the former question,
while a graph theoretical definition for the popularity concept
indicates a long-tailed, extreme value distribution. With these two
questions – and the answers thereto, the paper contributes to the
attempts to understand large-scale characteristics of malware at
the grand population level – at the level of the whole Internet.
Proceedings of 2016 European Intelligence and Security Informatics Conference (EISIC)